PENGARUH REWARD, MANAGER VALUE ORIENTATION TOWARD INNOVATION (VOI MANAJER) DAN KOMPETENSI KARYAWAN TERHADAP KINERJA KARYAWAN PADA PT. PLN (PERSERO) DISTRIBUSI LAMPUNG CABANG SRIBAHWONO - Rita Irviani; Ahmad Sidik (DINAMIKA: Jurnal Manajemen Akuntansi, Bisnis dan Kewirausahaan, 2019)
The purpose of this study is to support the awarding, VOI Managers and employee competencies on employee performance at PT. PLN (Persero) Distribution of Lampung branch of Sribahwono. The research method used is to use quantitative descriptive research methods. The population in this study were employees of PT. PLN (Persero) Distribution of Lampung sribahwono branch which distributed 13 people. The samples taken in this study were 13 people from all employees of PT. PLN (Persero) Distribution of Lampung Sribahwono branch. The sampling technique uses non-probability sampling using saturated samples or often called total sampling. The analysis technique used in this study is the Multiple Linear Regression Model. The results showed there was an influence on employee performance, there was an increase in VOI Managers on employee performance, and there was an increase in employee competence on the performance of employees of PT. PLN (Persero) Distribution of Lampung branch of Sribahwono.